2021
DOI: 10.1096/fj.202000393r
|View full text |Cite
|
Sign up to set email alerts
|

WBP2 promotes gastric cancer cell migration via novel targeting of LATS2 kinase in the Hippo tumor suppressor pathway

Abstract: Dysregulation of signaling pathways is responsible for many human diseases. The lack of understanding of the molecular etiology of gastric cancer (GC) poses a substantial challenge to the development of effective cancer therapy. To better understand the molecular mechanisms underlying the pathogenesis of GC, which will facilitate the identification and development of effective therapeutic approaches to improve patient outcomes, mass spectrometry-based phosphoproteomics analysis was performed to map the global … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(26 citation statements)
references
References 71 publications
1
25
0
Order By: Relevance
“…In a similar fashion, elevated WBP2 protein expression was also observed in the more aggressive gastric cancer cell lines as compared to the less aggressive ones [71]. Concurrently, in vitro and in vivo studies demonstrated that WBP2 was a promoter of cancer proliferation, migration and invasion [70][71][72][73][74]. In glioma cells, WBP2 regulates α enolase-mediated glycolysis to aggravate cell proliferation and migration [74].…”
Section: Wbp2 Expression and Impact On Cancersmentioning
confidence: 70%
See 4 more Smart Citations
“…In a similar fashion, elevated WBP2 protein expression was also observed in the more aggressive gastric cancer cell lines as compared to the less aggressive ones [71]. Concurrently, in vitro and in vivo studies demonstrated that WBP2 was a promoter of cancer proliferation, migration and invasion [70][71][72][73][74]. In glioma cells, WBP2 regulates α enolase-mediated glycolysis to aggravate cell proliferation and migration [74].…”
Section: Wbp2 Expression and Impact On Cancersmentioning
confidence: 70%
“…The oncogenic roles of WBP2 were initially studied in breast cancer and subsequently explored in other cancers such as squamous cell carcinoma, brain, liver, gastric and lung cancers. Figure 3B summarises some of the key evidence that positions WBP2 as a driver Besides breast cancer, WBP2 overexpression has also been observed in tumours of the liver, stomach, lung and skin, compared to adjacent normal tissues, through IHC experiments [70][71][72][73]. Furthermore, WBP2 status was positively associated with higher pathological stages and poorer survival in human glioma, gastric and non-small cell lung carcinoma (NSCLC) patients [25,71,72] (Figure 3B).…”
Section: Wbp2 Expression and Impact On Cancersmentioning
confidence: 84%
See 3 more Smart Citations